(untitled) (Research, Society and Development, 2023)
The following article aims to reflect about the place of subjectivity in the construction of the urban imaginary that surrounds cities, using a multifaceted literary contribution to compose its empirical work. Initially, the article is dedicated to a discussion based on Merleau Ponty (2004), about the perceived world, that is, the universe of investigation of the senses, in art, painting, philosophy and literature, which helps to clarify our understanding of historical events and the city; and in Bachelard’s idea of imaginary, fundamentally with regard to the work The poetics of space (2008), in which the author conceives space as “an instrument of analysis for the human soul” (2008). Then, and from this dialectical way of looking at the built space, we work with the hypothesis of some authors such as Canclini (1997), Bollas (2000) and Leitão (1998, 2011, 2012, 2021), that thinking about cities permeates, inseparably , the immaterial relationship between individuals and the urban space. Finally, supported by this recent theoretical discussion, which goes beyond conceptual limits and enters the literary universe to compose methodological analyses, we argue that the urban physical aspects in which we live are also imagistic and particular expressions of existing in the world.